Where and why do firms choose to move? Empirical evidence from Norway - Oyvind Lervik Nilsen; Trude Tørset; María Díez Gutiérrez; Elisabetta Cherchi; Stig Nyland Andersen (Journal of Transport and Land Use, 2020)
A key goal for many public policies is to increase the competitiveness of local industries and make areas more attractive for firm location and development. However, little is known about firm relocations even though they are of crucial importance in understanding economic development within a region and the effectiveness of the policies proposed. This paper contributes to filling this gap by looking further into the firm relocation process by estimating models for the decision to relocate and to where. The studied area consists of four counties on the western coast of Norway that generate about half of Norway’s traditional exports. Changes in firm relocations for approximately 16,500 firms within this study area are analyzed. In addition, interviews with firms that relocated are also carried out to support the findings from the model. The results indicate that the decision to relocate is influenced by a firm’s internal and external characteristics such as agglomeration. The results are relevant for regional planning and development as firms seem to have different preferences regarding what makes a location attractive or not. The results might serve as input in land-use interaction models, where changes in firm location patterns from transport investments are estimated.